Pengaruh SePENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER DELIGHT SEBAGAI VARIABEL MEDIASIrvice Quality Terhadap Customer Loyalty Dengan Customer Delight Sebagai Variabel Mediasi - Putra, I Gusti Jaya Khrisna; Suparna, Gede (E-Jurnal Manajemen; Vol 9 No 1 (2020)DO - 10.24843/EJMUNUD.2020.v09.i01.p20, 2020)
The purpose of this study was to analyze the effect of service quality on customer loyalty with customer delight as a mediating variable. This research was conducted at Gardin Bistro & Patisserie Seminyak Bali with Path Analysis data analysis techniques. The sample size obtained by using purposive sampling method as many as 130 respondents. Based on the results of the analysis it can be stated that Service quality has a positive and significant effect on customer loyalty, service quality has a positive and significant effect on customer delight, customer delight has a positive and significant effect on customer loyalty. The results of the study also found that customer delight mediated the influence of service quality on customer loyalty positively and significantly. Gardin Bistro & Patisserie Seminyak Bali needs to rejuvenate the facilities provided and improve the appearance of staff by providing work clothes every year so that the employees are clean and tidy. Management must re-educate every staff who works by providing service training so that they can better serve consumers. Keywords : service quality, customer delight, customer loyalty